2023
DOI: 10.1021/acsami.3c05619
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrochemical Performance of Disordered Rocksalt Cathodes Enabled by a Graphite Conductive Additive

Abstract: Cobalt-free cation-disordered rocksalt (DRX) cathodes are a promising class of materials for next-generation Li-ion batteries. Although they have high theoretical specific capacities (>300 mA h/g) and moderate operating voltages (∼3.5 V vs Li/Li + ), DRX cathodes typically require a high carbon content (up to 30 wt %) to fully utilize the active material which has a detrimental impact on cell-level energy density. To assess pathways to reduce the electrode's carbon content, the present study investigates how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Moreover, Han et al observed that carbon black additives facilitated an open electrode structure in lithium–sulfur batteries, whereas graphene nanosheets resulted in a closed structure, emphasizing the significance of carbon additives not only in the electronic properties but also in influencing the electrode structure. Likewise, the impact of carbon conductive additives on electrode structure was reported in disordered rocksalt (DRX) cathodes, noting that graphite additive yields a homogeneous distribution of the active material and conductive carbon throughout the electrode …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Han et al observed that carbon black additives facilitated an open electrode structure in lithium–sulfur batteries, whereas graphene nanosheets resulted in a closed structure, emphasizing the significance of carbon additives not only in the electronic properties but also in influencing the electrode structure. Likewise, the impact of carbon conductive additives on electrode structure was reported in disordered rocksalt (DRX) cathodes, noting that graphite additive yields a homogeneous distribution of the active material and conductive carbon throughout the electrode …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the impact of carbon conductive additives on electrode structure was reported in disordered rocksalt (DRX) cathodes, noting that graphite additive yields a homogeneous distribution of the active material and conductive carbon throughout the electrode. 9 Although carbon plays a significant role in the performance of lithium-ion batteries, its surface reactivity has been revealed in recent years and has been recognized as a major contributor to the decomposition of electrolyte at the electrode/electrolyte interface. 10 This is due to the high surface area of common carbonaceous materials used as conducting agents like carbon black, e.g., 67 m 2 g −1 for Super C45 and 87 m 2 g −1 for Super C65, 11 plus the various functional groups attached to their surface, such as carbonyl, carboxyl, and aromatic groups, that react readily upon contact with the electrolyte and during electrochemical cycling.…”
Section: ■ Introductionmentioning
confidence: 99%